BIOINFORMATICS ANALYSIS OF CODON USAGE BIAS AND RNA SECONDARY STRUCTURES FOR SALT STRESS RESPONSIVE GENES IN ARABIDOPSIS THALIANA AND SOLANUM LYCOPERSICUM - B. Sadia; W. N. Hamzazai; I. A. Baloch; S. Kazmi; Asyia; P. S. Jan; S. Irfan (Journal of Animal and Plant Sciences, 2018)
Salt stress is one of the most important abiotic stresses for agricultural crops and other plants. Salinity highly affects physical, physiological and metabolic responses of plants. Codon usage bias (CUB) and RNA secondary structures (RSS) were analyzed for salt stress responsive ( SSR) genes of Arabidopsis thaliana and Solanum lycopersicum. Four salt stress resistant genes SOS1 (salt overly sensitive 1), BZIP (basic lucien zipper protein), HVA22-like protein and CDPK1 (calcium-dependent protein kinase 1) of Arabidopsis thaliana as well as Solanum lycopersicum were compared for CUB and RSS. All genes expressed similarity for codon usage, as both plants showed to prefer more than 50% (65%, 50%, 60%, and 80%) similar codon usage for all four selected salt stress responsive genes. RSS analysis revealed that three SSR genes had significant difference in minimum free energy ( MFE) while two differed in number of loops and stems depicting overall mix behavior. These findings can further help to engineer the salt resistant genes by adjusting the codon usage through genetic screening and by using bioinformatics tools. of base pairing within a single molecule as well as in a set
Keywords: Codon usage bias; Genetic code; Salinity responsive genes; Secondary structure.